Passive drag in Para swimmers with physical impairments: Implications for evidence-based classification in Para swimming - Hogarth, L.; Oh, Y.-T.; Osborough, C.; Osborough, C.; Formosa, D.; Hunter, A.; Alcock, A.; Burkett, B.; Payton, C. (Scandinavian Journal of Medicine & Science in Sports, 2021)
The inherent hydrodynamic resistance force, or passive drag, of a swimmer directly influences how they move through the water. For swimmers with physical impairments, the strength of association between passive drag and swimming performance is unknown. Knowledge on this factor could improve the World Para Swimming classification process. This study established the relationship between passive drag and 100 m freestyle race performance in Para swimmers with physical impairments. Using a cross-sectional study design, an electrical-mechanical towing device was used to measure passive drag force in 132 international-level Para swimmers. There was a strong, negative correlation between normalized passive drag force and 100 m freestyle race speed in the combined participant cohort (Rho = -0.77, p < 0.001). Type of physical impairment was found to affect the relationship between passive drag and 100 m freestyle race speed when included in linear regression (R2 = 0.65, chi2 = 11.5, p = 0.025). These findings contribute to the body of evidence that passive drag can provide an objective assessment of activity limitation in Para swimmers with physical impairments. The effect of physical impairment type on the relationship between passive drag and swimming performance should be accounted for in Para swimming classification.